Composite lithium supplementing material, preparation method thereof and secondary battery
By using a composite lithium supplement material composed of lithium-rich material and dispersant residue in the secondary battery, the problem of poor dispersion of lithium-rich material is solved, and the life and performance of the battery are improved.
Patent Information
- Application Number
- CN202411735092.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
In the prior art, the dispersion of lithium-rich materials is poor, which leads to easy agglomeration during the preparation process, affecting the life and performance of the secondary battery.
A composite lithium supplement material is used, which consists of lithium-rich material and dispersant residues, which include oligomers and carbon materials. The dispersant is converted into dispersant residues through calcination treatment to improve the dispersibility of the material.
The dispersion of composite lithium supplement material is improved, material agglomeration is reduced, the particle size of lithium-rich materials is stabilized, the decomposition voltage and overpotential of the battery are reduced, and the battery life is extended.
Smart Images

Figure CN119560565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] During the first charge and discharge of a liquid lithium-ion battery, the lithium ions released from the positive electrode material react with the electrolyte to form a solid electrolyte interface (SEI) on the surface of the negative electrode material. This process will irreversibly consume more than 10% of the lithium source in the positive electrode material, making the first-week coulomb efficiency of the lithium-ion battery less than 90%, and will continue to consume the active lithium in the positive electrode during the charge and discharge cycle of the lithium-ion battery, resulting in a shortened life of the lithium-ion battery.
[0003] The current solution to this problem is to add appropriate lithium-rich materials (lithium-supplementing materials) to the positive electrode active materials, and reduce lithium loss during the cycle by releasing active lithium through the decomposition of the lithium-rich materials during battery charging. However, in the prior art, lithium-rich materials all have the problem of poor dispersibility, which makes the lithium-rich materials easy to agglomerate during the preparation process, or after mixing the lithium-rich materials with the positive electrode active materials, the lithium-rich materials and the positive electrode active materials agglomerate, so how to solve this problem has become the key. Summary of the invention
[0004] The purpose of the present invention is to provide a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problem of poor dispersibility of lithium-rich materials.
[0005] To achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a composite lithium supplement material, comprising a lithium-rich material and a dispersant residue, wherein the dispersant residue is bound to the surface of the lithium-rich material, and the dispersant residue comprises an oligomer, and the molecular weight of the oligomer is 500 to 10,000.
[0007] In one embodiment, the dispersant residue further includes a carbon material, the carbon material is formed by carbonizing the dispersant, and the carbon material and the oligomer are mixed and coated on the surface of the lithium-rich material.
[0008] In one embodiment, the oligomer and / or the carbon material is a linear structure, and / or the oligomer and / or the carbon material are interwoven to form a network structure.
[0009] In one embodiment, the lithium-rich material is a porous structure having pits on the surface, and the oligomer and / or the carbon material extends into a plurality of the pits to connect the plurality of pits in series.
[0010] In one embodiment, at least one of the pits contains a portion of the oligomer and / or the carbon material, and the oligomer and / or the carbon material are mixed in the pit.
[0011] In one embodiment, the ratio of the depth of the pit to the diameter of the pit is (1-10):(99-90).
[0012] In one embodiment, the length of the linear structured oligomer or the carbon material is 50 nm to 1000 nm.
[0013] In one embodiment, the coating thickness of the carbon material and the oligomer is 50 nm to 500 nm.
[0014] In one embodiment, the composite lithium supplementing material further includes a catalyst, and the catalyst is combined on the surface of at least one of the lithium-rich material, the oligomer and the carbon material to form a single atomic film.
[0015] In one embodiment, the dispersant residue includes small molecule organic matter and / or inorganic carbonate.
[0016] In one embodiment, the catalyst includes a metal element and / or a metal compound.
[0017] In one embodiment, the mass ratio of the lithium-rich material, the oligomer, the carbon material and the catalyst is (70-97): (5-15): (1-10): (1-5).
[0018] In one embodiment, the particle size of the lithium-rich material is 500 nm to 20 μm.
[0019] In one embodiment, the porosity of the lithium-rich material is 20% to 80%.
[0020] In one embodiment, the specific surface area of the lithium-rich material is 500 m 2 / g~2000m 2 / g.
[0021] In a second aspect, the present invention provides a method for preparing a composite lithium-supplementing material, comprising: mixing a lithium-rich material with a dispersant to obtain a mixture; calcining the mixture to convert at least a portion of the dispersant into a dispersant residue to obtain a composite lithium-supplementing material; wherein the dispersant residue includes an oligomer, and the molecular weight of the oligomer is 500 to 10,000.
[0022] In a third aspect, the present invention further provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the composite lithium supplement material as described in the first aspect, or comprises the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material as described in the second aspect.
[0023] In view of the problems existing in the prior art, the present invention provides a composite lithium-supplementing material with dispersant residues, and the composite lithium-supplementing material has the following effects: the dispersant residues combined on the surface of the lithium-rich material have a dispersing function, which can improve the dispersibility of the composite lithium-supplementing material itself, reduce the agglomeration of the composite lithium-supplementing material, and reduce the amount of additional dispersant in the slurry; and the dispersant residues combined on the surface of the lithium-rich material can also prevent the lithium-rich material from agglomerating, ensuring that the lithium-rich material remains in a nano state during the processing process, which not only stabilizes the particle size of the lithium-rich material, but also reduces the gel phenomenon during the application of the lithium-rich material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 is a schematic cross-sectional view of a composite lithium supplement material according to an embodiment;
[0026] Figure 2 is a top view of a lithium-rich material, an oligomer, and a carbon material according to an embodiment;
[0027] Figure 3 is a schematic diagram of a partial structure of a composite lithium supplement material according to an embodiment;
[0028] Figure 4 The present invention is a flow chart of a method for preparing a composite lithium supplement material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.
[0031] It should be noted that the "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] All steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.
[0033] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0034] Oligomer: refers to a polymer composed of fewer repeating units. Its relative molecular mass is between small molecules and macromolecules.
[0035] Thermal decomposition of polymers: Thermal decomposition of polymer materials is mainly due to the fact that the molecular chains are subjected to heat energy at high temperatures, which causes the chemical bonds between molecules to break, resulting in a decrease in molecular weight. This phenomenon usually occurs above the glass transition temperature of the material, that is, when the material changes from a glassy state to a rubbery state or a viscous flow state. The final products of thermal decomposition of hydrocarbon polymers are carbon and hydrogen, as well as low-level hydrocarbons and asphalt.
[0036] The present invention provides a composite lithium supplement material, please refer to Figure 1-Figure 3 .
[0037] In one implementation, please refer to Figure 1 The composite lithium supplement material includes a lithium-rich material 10 and a dispersant residue, the dispersant residue is combined on the surface of the lithium-rich material 10, and the dispersant residue includes an oligomer 20, and the molecular weight of the oligomer 20 is 500-10000.
[0038] Specifically, the lithium-rich material 10 is the main body for lithium supplementation, which can contribute a large amount of lithium ions. During the first charging process, the lithium (Li) in the lithium-rich material 10 can be released and migrated to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, thereby increasing the total capacity and energy density of the battery. However, most of the existing commonly used lithium-rich materials 10 have the problem of poor dispersibility, which causes the lithium-rich material 10 to easily agglomerate during the preparation process, or after the lithium-rich material 10 is mixed with the positive electrode active material, the lithium-rich material 10 and the positive electrode active material agglomerate, so how to solve this problem has become the key.
[0039] In view of the problems existing in the prior art, the present invention provides a composite lithium-supplementing material with dispersant residues, and the composite lithium-supplementing material has the following effects: the dispersant residues combined on the surface of the lithium-rich material 10 have a dispersing function, which can improve the dispersibility of the composite lithium-supplementing material itself, reduce the agglomeration of the composite lithium-supplementing material, and reduce the amount of additional dispersant in the slurry; and the dispersant residues combined on the surface of the lithium-rich material 10 can also prevent the lithium-rich material 10 from agglomerating, ensuring that the lithium-rich material 10 remains in a nano state during the processing process, which not only stabilizes the particle size of the lithium-rich material 10, but also reduces the gel phenomenon during the application of the lithium-rich material 10.
[0040] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li x1 C y1 O z1 , where 0<x1≤2,y1> 0, z1>0. In a specific embodiment, the lithium-rich material 10 may include Li 2 C 2 O 4 (lithium oxalate), Li 2 CO 3 (lithium carbonate), Li 2 C3 O 3 (Lithium trimesate), Li 2 C 4 O 4 (Lithium butynedioate), Li 2 C 6 O 6 、Li 2 C 3 O 5 (Lithium pyruvate), and Li 2 C 4 O 6 or more of those in. It can be understood that the above-mentioned lithium-rich materials 10 are all materials with a high decomposition voltage. A relatively high voltage will cause oxygen to be generated during the first charge and discharge of the lithium-ion battery. The generated oxygen will further oxidize and cause the electrolyte to oxidize and decompose, thereby reducing the safety and performance of the lithium-ion battery. Therefore, the solution provided by the present invention can be applied to such materials.
[0041] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li x2 M y2 O z2 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1 ≤ x2 ≤ 8, 0 < y2, 0 < z2 < 7. In a specific embodiment, the lithium-rich material 10 may include Li 5 FeO 4 、Li 6 MnO 4 、Li 6 CoO 4 、Li 6 ZnO 4 、Li 2 NiO 2 、Li 2 CuO 2 、Li 2 CoO 2 、Li 2 MnO 2 、Li 2 Ni 0.5 Mn 1.5 O 4 、Li 2 Ni d Cu (1-d) O 2 (0 < d < 1), etc.
[0042] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li x3 K y3, where K is at least one element among O, S, P, N, F, B, Se, Te, 1 ≤ x3 ≤ 5, 0 < y3. The binary lithium supplement includes but is not limited to Li 2 O, Li 2 O 2 , Li 3 N, Li 2 S, LiF, Li 3 P, Li 2 Se, etc.
[0043] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li 1+x4 A y4 O z4 , where 0 < x4 ≤ 1.2, 1 ≤ y4 < 3, z4 > 0, and A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, Mg. These lithium-rich materials 10 can be used as both lithium supplements and directly as cathode materials. Exemplarily, the lithium-rich material 10 includes Li 2 CuO 2 , Li 2 NiO 2 , Li 2 MnO 2 , etc.
[0044] In one embodiment, the lithium-rich material 10 may further include LiOH (lithium deintercalation potential 4.8V), Li 4 SiO 4 (lithium deintercalation potential 4.5V), Li 3 PO 4 (lithium deintercalation potential exceeding 4V). The deintercalation of lithium from these materials requires a relatively high charging voltage, which will cause oxygen to be generated during the first charge and discharge of the lithium-ion battery. The generated oxygen further oxidizes and decomposes the electrolyte, resulting in a reduction in the safety and performance of the lithium-ion battery. Therefore, the solution provided by the present invention is applicable to such materials.
[0045] In one embodiment, the above-mentioned lithium-rich material 10 can be undoped or doped and modified, or can be surface-coated, pre-lithiated, etc. These lithium-rich materials 10 have high theoretical capacity and structural stability, can provide abundant lithium ions, effectively supplement the irreversible lithium ions consumed by the formation of the SEI film on the negative electrode, and improve the first efficiency and overall electrochemical performance of the battery.
[0046] In one embodiment, the dispersant residue is a product obtained by cracking the dispersant after calcination. The preferred dispersant is a high molecular polymer, so the dispersant residue includes an organic compound (i.e., oligomer 20) having a molecular weight less than that of the original dispersant. It should be explained that the dispersant residue needs to be distinguished from the method of preparing a carbon coating layer using a high molecular polymer as a carbon source in the prior art. The dispersant residue in the present invention cannot be simply understood as a carbon material, and the oligomer 20 in the dispersant residue is essentially an organic compound. Under the preset calcination environment, the oligomer 20 can be understood as an intermediate product of the dispersant and the carbon material. The oligomer 20 retains the characteristics of the dispersant, and the thermal decomposition process enables the oligomer 20 to have conductivity that the dispersant does not have.
[0047] In one implementation, please refer to Figure 1 The dispersant residue also includes a carbon material 30, which is formed by carbonizing the dispersant. The carbon material 30 and the oligomer 20 are mixed and coated on the surface of the lithium-rich material 10. Specifically, since the oligomer 20 is obtained by thermal decomposition of the dispersant, part of the oligomer 20 is further thermally decomposed to form the carbon material 30, and the oligomer 20 and the carbon material 30 are mixed and coated on the outer surface of the lithium-rich material 10 to form a coating layer.
[0048] The advantage of the composite lithium-replenishing material of the present invention also including carbon material 30 is that the conductivity of the lithium-rich material 10 is further improved by the carbon material 30, because the carbon material 30 has a higher conjugated structure than the oligomer 20, thereby providing stronger conductivity; and the carbon material 30 coating provided by the present invention is lower in coating thickness of the carbon material 30 and the oligomer 20 than that of the prior art, and only a small amount of oligomer 20 and carbon material 30 are used to play both a conductive and a dispersing role, the mass proportion of the lithium-rich material 10 in the composite lithium-replenishing material is higher, and the lithium-replenishing capacity is higher.
[0049] In one embodiment, the dispersant residue also includes small molecule organic matter and / or inorganic salt. It is understandable that, based on the molecular structure and elemental composition of the polymer dispersant, small molecule organic matter or inorganic salt may also be produced during its thermal decomposition. Among them, small molecule organic matter includes small molecule alkanes (such as ethane, propane, butane, etc.), and also includes some organic small molecules containing functional groups (such as hydroxyl, carboxyl, etc.). Inorganic salts are formed by the combination of metals and organic matter in lithium-rich materials (such as inorganic lithium salts), or are formed by organic matter containing metal ligands.
[0050] In one implementation, please refer to Figure 2, the oligomer 20 and / or the carbon material 30 are linear structures. Specifically, the linear structure includes nanowires, nanotubes, nanorods, nanofibers, etc. In a specific embodiment, the linear structure can be a nanofiber, and the nanofiber includes a polymer nanofiber (oligomer 20) and a carbon nanofiber, wherein the carbon nanofiber is obtained by further carbonizing the polymer nanofiber. The outer surface of the lithium-rich material 10 is wrapped with a plurality of linear oligomers 20 and carbon materials 30; and the plurality of linear oligomers 20 and carbon materials 30 can be independent of each other.
[0051] In one implementation, please refer to Figure 1 , the oligomer 20 and / or the carbon material 30 are interwoven to form a network structure. Specifically, the oligomer 20 and the carbon material 30 form a "fishnet"-like structure. In a specific embodiment, the oligomer 20 can independently form a network structure at a portion of the outer surface of the lithium-rich material 10, or the carbon material 30 can independently form a network structure at a portion of the outer surface of the lithium-rich material 10, or the oligomer 20 and the carbon material 30 can be mixed and jointly form a network structure at a portion of the outer surface of the lithium-rich material 10.
[0052] In one embodiment, the particle size of the lithium-rich material 10 is 500nm to 20μm. When the particle size of the lithium-rich material 10 is within the above range, the conductivity and decomposition degree of the lithium-rich material 10 can be ensured. When the particle size of the lithium-rich material 10 is too small, it will increase the difficulty of preparing the lithium-rich material 10, and it will increase the difficulty of making pits 11 on the lithium-rich material 10, and it will be difficult to obtain a material with a high specific surface area of pits 11. When the particle size of the lithium-rich material 10 is too large, the conductivity of the lithium-rich material 10 will deteriorate, and it will be unfavorable to improve the decomposition degree of the lithium-rich material 10 and the release of lithium ions. Optionally, the particle size of the lithium-rich material 10 can be 500nm, 800nm, 1μm, 2μm, 5μm, 10μm, 15μm, 20μm.
[0053] In one embodiment, the lithium-rich material 10 is a porous structure, and the porosity of the lithium-rich material 10 is 20% to 80%. When the porosity of the lithium-rich material 10 is within the above range, the structural stability of the lithium-rich material 10 can be ensured, as well as the specific surface area of the lithium-rich material 10. When the porosity of the lithium-rich material 10 is too small, there are too few pits 11 or the pits 11 are unevenly distributed, resulting in a small specific surface area of the lithium-rich material 10. When the porosity of the lithium-rich material 10 is too large, the structural stability of the lithium-rich material 10 deteriorates, and the overall strength of the composite lithium-supplementing material deteriorates. Optionally, the porosity of the lithium-rich material 10 can be 20%, 30%, 40%, 50%, 60%, 70%, or 80%.
[0054] In one embodiment, the specific surface area of the lithium-rich material 10 is 500 m 2 / g~2000m 2 / g. Satisfying the specific surface area of the lithium-rich material 10 within the above range is conducive to the decomposition of the lithium-rich material 10 and ensuring that the lithium-rich material 10 is in full contact with the oligomer 20 and the carbon material 30. When the specific surface area of the lithium-rich material 10 is too small, the decomposition effect of the lithium-rich material 10 deteriorates, and at the same time, the contact between the lithium-rich material 10 and the oligomer 20 and the carbon material 30 deteriorates, and the conductivity of the lithium-rich material 10 cannot be effectively improved and its decomposition voltage cannot be reduced. Optionally, the specific surface area of the lithium-rich material 10 can be 500m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g、1800m 2 / g, 2000m 2 / g.
[0055] In one implementation, please refer to Figure 1 The lithium-rich material 10 is a porous structure with pits 11 on the surface. Specifically, the pits 11 on the surface of the lithium-rich material 10 can expand its own specific surface area. The high specific surface area is conducive to the decomposition of the lithium-rich material 10. At the same time, due to the high specific surface property, the lithium-rich material 10 is easy to combine with the oligomer 20 and the carbon material 30, which increases the contact area and can greatly reduce the decomposition voltage of the lithium-rich material 10. At the same time, due to the high specific surface property, the particle size of the lithium-rich material 10 is reduced in disguise, the conductivity of the lithium-rich material 10 is enhanced, and the decomposition degree of the lithium-rich material 10 is improved.
[0056] In one implementation, please refer to Figure 2 , the lithium-rich material 10 is a honeycomb porous structure, and the honeycomb porous structure includes macropores and micropores. The macropores are evenly distributed on the outer surface of the lithium-rich material 10, and the micropores are distributed on the outer surface of the lithium-rich material 10 and / or the micropores are distributed on the inner wall of the macropores. Specifically, the honeycomb porous structure means that the outer surface of the lithium-rich material 10 forms a "grid-like" porous structure, thereby increasing the specific surface area of the lithium-rich material 10. Among them, the honeycomb porous structure includes macropores and micropores, and the pore size of the macropores is larger than the pore size of the micropores. The macropores are evenly distributed on the outer surface of the lithium-rich material 10, and the micropores can be distributed on the outer surface of the lithium-rich material 10 or on the inner wall of the macropores. Among them, the micropores distributed on the inner wall of the macropores and the macropores together constitute a composite structure of multi-level pores, which can further increase the specific surface area of the lithium-rich material 10.
[0057] In one implementation, please refer to Figure 1, the oligomer 20 and / or the carbon material 30 extend into the plurality of pits 11 to connect the plurality of pits 11 in series. Specifically, based on the above-mentioned embodiment, the outer surface of the lithium-rich material 10 is wrapped with a plurality of linear oligomers 20 and carbon materials 30, and the plurality of pits 11 on the lithium-rich material 10 are connected in series through the linear materials. It should be explained that the linear materials connecting the plurality of pits 11 in series means that the linear materials can penetrate into and out of the plurality of pits 11.
[0058] The present invention connects multiple pits 11 in series through linear materials, which can not only improve the conductivity of the lithium-rich material 10, but also enhance the enhancement effect of the lithium-rich material 10; and the unique one-dimensional characteristics of the linear material will not affect the specific surface area of the lithium-rich material 10.
[0059] In one implementation, please refer to Figure 1 , at least one of the pits 11 contains a portion of the oligomer 20 and / or the carbon material 30, and the oligomer 20 and / or the carbon material 30 are mixed in the pit 11. Specifically, a plurality of linear materials may be inserted into the same pit 11, and the inserted linear materials are interwoven in the pit 11; thus, the pit 11 and the linear materials together form a "cave-spider web"-like structure.
[0060] In one embodiment, the ratio of the depth of the pit 11 to the diameter of the pit 11 is (1 to 10): (99 to 90). When the ratio of the depth to the diameter of the pit 11 is within the above range, the structural stability of the lithium-rich material 10 can be ensured, as well as the contact area between the lithium-rich material 10, the oligomer 20 and the carbon material 30, and the conductivity and decomposition degree of the lithium-rich material 10 can be ensured. When the ratio of the depth to the diameter of the pit 11 is too small, it means that the diameter of the pit 11 is too large and the depth is too shallow, and the purpose of increasing the specific surface area cannot be achieved, and the contact sites between the oligomer 20, the carbon material 30 and the lithium-rich material 10 become fewer. When the ratio of the depth to the diameter of the pit 11 is too large, it means that the depth of the pit 11 is too large and the diameter is too small, so that the pit 11 becomes a pore, and the oligomer 20 is contained in the pore. When it is mixed with the positive electrode active material in the later stage, the oligomer 20 is difficult to escape, and thus cannot play a dispersing role. Optionally, the ratio of the depth of the pit 11 to the diameter of the pit 11 can be 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, or 10:90.
[0061] In one embodiment, the coating thickness of the oligomer 20 and the carbon material 30 is 50nm to 500nm. When the coating thickness of the oligomer 20 and the carbon material 30 is within the above range, the conductivity of the composite lithium supplement material and the capacity of the composite lithium supplement material can be ensured. When the coating thickness of the oligomer 20 and the carbon material 30 is too thin, the conductivity of the composite lithium supplement material decreases, and the confinement effect of the oligomer 20 and the carbon material 30 on the lithium-rich material 10 becomes worse, and the particle size of the lithium-rich material 10 is too large. When the coating thickness of the oligomer 20 and the carbon material 30 is too thick, the lithium supplement capacity of the composite lithium supplement material will decrease. Optionally, the coating thickness of the oligomer 20 and the carbon material 30 can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm.
[0062] In one embodiment, the length of the oligomer 20 or carbon material 30 with a linear structure is 50nm to 1000nm. When the length of the oligomer 20 or carbon material 30 is within the above range, the structural stability of the composite lithium supplement material after discharge can be ensured, as well as the conductivity of the composite lithium supplement material. When the length of the oligomer 20 or carbon material 30 is too small, the structural stability of the composite of the oligomer 20 or carbon material 30 deteriorates, resulting in pits 11 still appearing in the pole piece after the lithium-rich material 10 is discharged, and it is difficult for the oligomer 20 or carbon material 30 to connect multiple pits in series. When the length of the oligomer 20 or carbon material 30 is too large, the coating thickness of the oligomer 20 or carbon material 30 is too thick, and the conductivity deteriorates. Optionally, the length of the oligomer 20 or carbon material 30 with a linear structure can be 50nm, 100nm, 200nm, 400nm, 600nm, 800nm, or 1000nm.
[0063] In one implementation, please refer to Figure 1 The composite lithium-replenishing material also includes a catalyst 40, which is combined on the surface of at least one of the lithium-rich material 10, the oligomer 20 and the carbon material 30 to form a single atomic film. Specifically, the catalyst 40 includes a metal element and / or a metal compound. The catalyst 40 can be combined on the surface of the lithium-rich material 10, or filled in the pits 11 of the lithium-rich material 10; the catalyst 40 can also be combined on the surface of the oligomer 20 and the carbon material 30, or confined in the mesh of the oligomer 20 and the carbon material 30. The catalyst 40 combined on the lithium-rich material 10 can be used to reduce the decomposition voltage of the lithium-rich material 10. The catalyst 40 combined on the oligomer 20 and the carbon material 30 can be used to support the oligomer 20 and the carbon material 30, so that the oligomer 20, the carbon material 30 and the catalyst 40 form a three-dimensional hollow structure together. The catalyst 40 enhances the structural stability of the composite lithium-replenishing material and can prevent the pits 11 from appearing on the pole piece during the decomposition process of the composite lithium-replenishing material.
[0064] In one implementation, please refer to Figure 3, at least part of the catalyst 40 is combined with the inner wall of the pit 11 to form a single atomic film. Specifically, on the inner wall of the pit 11 of the lithium-rich material 10, the catalyst 40 forms a film layer that adheres to the inner wall, and the pit 11 will not be filled with the catalyst 40, and the lithium-rich material 10 will retain its rich honeycomb morphology. It should be explained that in the present invention, the particle size of the catalyst 40 is very small, and the catalyst 40 is deposited on the inner wall of the pit 11 in a single-atom manner, which is different from the solution of filling the pore structure in the prior art. The present invention only thinly covers the inner wall of the pit 11 of the lithium-rich material 10 with a layer of catalyst 40, and the pit 11 is not filled, so that the lithium-rich material 10 will retain its rich honeycomb morphology.
[0065] The present invention makes the catalyst 40 into a single atomic film on the inner wall of the pit 11, which not only allows the catalyst 40 to fully contact with the lithium-rich material 10 and utilizes the catalyst 40 to reduce the decomposition voltage of the lithium-rich material 10; it can also retain the rich honeycomb porous structure of the lithium-rich material 10, thereby ensuring the high specific surface area characteristics of the lithium-rich material 10, ensuring the contact between the lithium-rich material 10 and the oligomer 20 and the carbon material 30, and in disguised form reducing the particle size of the lithium-rich material 10, enhancing the conductivity of the lithium-rich material 10, and improving the decomposition degree of the lithium-rich material 10.
[0066] In one implementation, please refer to Figure 3 , the catalyst 40 is combined with the outer surface of the oligomer 20 and the carbon material 30 to form a single atomic film. Specifically, the catalyst 40 forms a film layer that adheres to the outer surface of the oligomer 20 and the carbon material 30 of the linear structure. By combining the catalyst 40 outside the oligomer 20 and the carbon material 30, the catalyst 40 can be used to support the oligomer 20 and the carbon material 30. The catalyst 40 enhances the structural stability of the oligomer 20 and the carbon material 30, which can prevent the oligomer 20 and the carbon material 30 from shrinking in volume and collapsing during the firing process, and can also prevent the formation of pits 11 in the pole piece during the decomposition of the lithium-rich material 10.
[0067] In one embodiment, the mass ratio of the lithium-rich material 10, the oligomer 20, the carbon material 30 and the catalyst 40 is (70-97): (5-15): (1-10): (1-5). When the mass ratio of the above four is within the above range, it can be ensured that the composite lithium-supplementing material has a large lithium-supplementing capacity, as well as the conductivity and low decomposition voltage of the material. When the mass proportion of the oligomer 20, the carbon material 30 or the catalyst 40 is too large, the content of the lithium-rich material 10 will be affected, thereby reducing the lithium-supplementing capacity of the composite lithium-supplementing material. When the mass proportion of the oligomer 20 and the carbon material 30 is too small, it is not conducive to improving the conductivity of the lithium-rich material 10, and the confinement effect of the oligomer 20 and the carbon material 30 on the lithium-rich material 10 becomes worse, and the dispersion of the composite lithium-supplementing material in the positive electrode slurry in the later stage becomes worse. When the mass proportion of the catalyst 40 is too small, the effect of the catalyst 40 catalyzing the decrease in the decomposition voltage of the lithium-rich material 10 becomes worse. Optionally, the mass ratio of the lithium-rich material 10, the oligomer 20, the carbon material 30 and the catalyst 40 can be 70: (5-15): (1-10): (1-5), 80: (5-15): (1-10): (1-5), 97: (5-15): (1-10): (1-5), (70-97): 5: (1-10): (1-5), (70-97): 10: (1-10): (1-5), (70-97) :15:(1~10):(1~5),(70~97):(5~15):1:(1~5),(70~97):(5~15):5:(1~5),(70~97):(5~15):10:(1~5),(70~97):(5~15):(1~10):1、(70~97):(5~15):(1~10):3、(70~97):(5~15):(1~10):5.
[0068] The present invention provides a method for preparing a composite lithium supplement material. Figure 4 .
[0069] In one embodiment, the preparation method of the composite lithium supplement material specifically comprises the following steps:
[0070] Step S10, mixing the lithium-rich material with a dispersant to obtain a mixture.
[0071] Step S20, calcining the mixture to convert at least a portion of the dispersant into a dispersant residue to obtain a composite lithium supplement material.
[0072] In one embodiment, in step S10, the lithium-rich material is mixed with a dispersant, specifically comprising: adding a dispersant and a stabilizer to an organic solvent to prepare a mixed liquid, adding the lithium-rich material to the mixed liquid, and performing a hydrothermal reaction at a high temperature to form a mixture.
[0073] In one embodiment, the dispersant may include a polymer material (such as a conductive polymer), specifically including but not limited to cellulose, polyacrylonitrile, polyester, polyimide, polyaniline, etc. It should be explained that the dispersant and stabilizer give the lithium-rich material a high dispersion property so that the lithium-rich materials will not agglomerate, and the lithium-rich materials form a preliminary network structure under the wrapping of the dispersant.
[0074] In one embodiment, in step S20, before calcining the mixture, the process may further include: depositing a catalyst on the mixture. Specifically, the catalyst is deposited on the lithium-rich material and the dispersant by ALD (atomic layer deposition technology). The product is then placed at a high temperature for calcination and carbonization, and the dispersant is converted into a dispersant residue, which may include oligomers, carbon materials, small molecular organic matter, and inorganic salts.
[0075] ALD technology can deposit the catalyst in the form of single atoms onto lithium-rich materials and dispersants, and the catalyst can form a single-atom film on the surface of the lithium-rich material. At the same time, the catalyst and dispersant combine to form a supporting structure for the lithium-rich material, enhancing the stability of the composite lithium-supplementing material. In addition, the dispersant is thermally decomposed or carbonized in situ to form a conductive network, which enhances the conductivity of the lithium-rich material and can prevent the agglomeration of lithium-rich materials, thereby enhancing the decomposition effect of the lithium-rich material.
[0076] In one embodiment, the method for preparing the composite lithium supplementing material, before mixing the lithium-rich material with the dispersant, further comprises:
[0077] Step S00, etching the lithium-rich material with an etchant to obtain a lithium-rich material with a porous outer surface.
[0078] In one embodiment, in step S00, an etchant is used to etch the lithium-rich material, specifically including: mixing the lithium-rich material and the etchant, the etchant is combined with the surface of the lithium-rich material, the etchant is nano-metal compound particles, and the mixture of the etchant and the lithium-rich material is placed in an inert atmosphere for thermal etching, so that a porous structure is etched on the surface of the lithium-rich material.
[0079] It should be explained that nano-metal compound particles can be used to mark the surface of lithium-rich materials in a dot-like manner, that is, multiple nano-metal compound particles are distributed in a star-like manner on the surface of lithium-rich materials. Then, at high temperatures, since metals absorb heat better, nano-metal compound particles absorb heat first and generate a large amount of heat at the marked positions, causing the marked positions of the lithium-rich materials to begin to decompose first. Since the marked positions decompose first and pits appear, the pore size and porosity of the pits on the surface of the lithium-rich material can be controlled by controlling the particle size and distribution density of the nano-metal compound particles.
[0080] Therefore, the etching method of the lithium-rich material provided in the present invention is solid-state etching, which is different from liquid etching, gas etching, etc. in the prior art. The solid-state etching method can prepare the above-mentioned honeycomb porous structure, and the pore structure is evenly distributed and the pore size is controllable.
[0081] In other embodiments, in step S10, the lithium-rich material may be etched by liquid etching, gaseous etching, etc. For example, if the lithium-rich material is a lithium-rich material containing a transition metal, water etching may be used. Since the lithium-rich material containing a transition metal has poor stability in water, water vapor may be used to etch its surface.
[0082] The present invention provides a method for preparing a composite lithium-supplementing material with dispersant residues, wherein a dispersant and a lithium-rich material are mixed to prepare a mixture, and after sintering, the dispersant is driven to be converted in situ into oligomers and carbon materials to obtain a composite lithium-supplementing material. The mixing of the dispersant and the lithium-rich material can avoid the agglomeration of the lithium-rich material, preserve the nano state during the processing process, not only stabilize the particle size of the lithium-rich material, but also reduce the gel phenomenon during the application of the lithium-rich material; and in the obtained composite lithium-supplementing material, the dispersant residue has a dispersing function. After the composite lithium-supplementing material is mixed with the positive electrode active material, the dispersant residue can improve the dispersibility of the composite lithium-supplementing material itself, reduce the agglomeration of the composite lithium-supplementing material, and reduce the amount of additional dispersant in the slurry; in addition, the dispersant residue is conducive to improving the specific surface area and conductivity of the lithium-rich material. Compared with the existing relatively thick carbon layer coated, only a small amount of dispersant residue can play both a conductive role and a dispersing role, and the content of the lithium-rich material will also increase.
[0083] Furthermore, the present invention also etches the surface of the lithium-rich material through an etching technique, so that the lithium-rich material forms a porous structure with a high specific surface area, and then deposits a catalyst on the surface of the lithium-rich material and the dispersant to obtain a composite lithium-supplementing material with pits and a catalyst. The lithium-rich material with a high specific surface area is conducive to decomposition. At the same time, since the lithium-rich material with a high specific surface area is easy to connect with the catalyst, oligomers and carbon materials, the contact area is increased, and the decomposition voltage of the lithium-rich material can be greatly reduced; at the same time, due to the high specific surface area characteristics, the particle size of the lithium-rich material is reduced, the conductivity of the lithium-rich material is enhanced, and the decomposition degree of the lithium-rich material is improved. Since the dispersant is reduced in volume during the sintering process, but supported by the catalyst, the two form a three-dimensional hollow structure, which enhances the structural stability of the composite lithium-supplementing material and can prevent pits from appearing in the pole piece during the decomposition process.
[0084] In one embodiment, the present invention further provides a positive electrode material, the positive electrode material comprising a positive electrode active material and a lithium supplement. The lithium supplement is a composite lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium vanadium phosphate fluoride, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0085] In one embodiment, the content of the composite lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of composite lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of composite lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the composite lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.
[0086] In one embodiment, the present invention further provides a positive electrode plate, the positive electrode plate includes a current collector and an active material layer disposed on the current collector, the active material layer includes the composite lithium supplement material of any one of the above embodiments. Or the active material layer includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material in the above embodiments.
[0087] In one embodiment, the positive electrode sheet includes a positive current collector, and the positive current collector has a positive active layer, and the positive active layer includes components such as positive active materials, composite lithium supplement materials, conductive agents, and binders. The present invention does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive active layer is 2wt% to 4wt%.
[0088] In one embodiment, the present invention further provides a secondary battery, the secondary battery comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode comprises the above-mentioned positive electrode material; the electrolyte may be an electrolyte solution, in which case the secondary battery further comprises a diaphragm disposed between the positive electrode plate and the negative electrode plate; or, the electrolyte may be a solid electrolyte solution, in which case the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0089] The technical solution of the present invention is described in detail below through specific embodiments.
[0090] Example 1
[0091] This embodiment provides a composite lithium supplement material. The composite lithium supplement material includes a lithium-rich material (Li 2 C 2 O 4 ), oligomers, carbon materials and catalysts (CoO). The surface of the lithium-rich material has pits.
[0092] The particle size of the lithium-rich material is 1 μm, the porosity of the lithium-rich material is 60%, and the specific surface area of the lithium-rich material is 800 m 2 / g, the ratio of the depth to the diameter of the pit is 5:95, the length of the oligomer and the carbon material is 200nm, the coating thickness of the oligomer and the carbon material is 80nm, and the mass ratio of the lithium-rich material, the oligomer, the carbon material and the catalyst is 90:3:3:4.
[0093] The preparation method of the composite lithium supplement material comprises the following steps:
[0094] 1) Li 2 C 2 O 4 Mixed with an etchant (nanometallic compound particles), the etchant is bound to the Li 2 C 2 O 4 The surface of the etchant and Li 2 C 2 O 4 The mixture is placed in an inert atmosphere and thermally etched to make Li 2 C 2 O 4 A porous structure is etched on the surface.
[0095] 2) Add dispersant (carboxymethyl cellulose) and stabilizer to the organic solvent to make a mixed solution, and 2 C 2 O 4 Add into the mixed solution and hydrothermally react at high temperature to form a mixture.
[0096] 3) CoO is deposited onto Li by ALD (atomic layer deposition technology) 2 C2 O 4 and dispersants, and then place the product under high temperature for calcination and carbonization, and the dispersant is converted into oligomers, carbon materials, small molecule alkanes and inorganic lithium salts.
[0097] Example 2
[0098] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the lithium-rich material, the oligomer, the carbon material and the catalyst is 81:5:10:4.
[0099] Example 3
[0100] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the mass ratio of the lithium-rich material, the oligomer, the carbon material and the catalyst is 80:15:1:4.
[0101] Example 4
[0102] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the coating thickness of the oligomer and the carbon material is 50 nm.
[0103] Example 5
[0104] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the coating thickness of the oligomer and the carbon material is 500 nm.
[0105] Example 6
[0106] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the length of the oligomer and the carbon material is 50 nm.
[0107] Example 7
[0108] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the length of the oligomer and the carbon material is 1000 nm.
[0109] Example 8
[0110] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the depth to diameter ratio of the pit is 1:99, the porosity of the lithium-rich material is 20%, and the specific surface area of the lithium-rich material is 500m 2 / g.
[0111] Example 9
[0112] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the depth to diameter ratio of the pit is 10:90, the porosity of the lithium-rich material is 70%, and the specific surface area of the lithium-rich material is 1200m2 / g.
[0113] Example 10
[0114] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the lithium-rich material is 500 nm.
[0115] Embodiment 11
[0116] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the particle size of the lithium-rich material is 20 μm.
[0117] Example 12
[0118] This embodiment provides a composite lithium-supplementing material. The difference between this embodiment and embodiment 1 is that the surface of the lithium-rich material is flat and has no pits.
[0119] Embodiment 13
[0120] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the composite lithium supplement material does not include carbon material.
[0121] Embodiment 14
[0122] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the composite lithium supplement material does not include a catalyst.
[0123] Embodiment 15
[0124] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the lithium-rich material is replaced by lithium acrylate.
[0125] Example 16
[0126] This embodiment provides a composite lithium supplement material. The difference between this embodiment and embodiment 1 is that the catalyst is replaced by Co 3 O 4 .
[0127] Comparative Example 1
[0128] This comparative example provides a lithium-rich material Li 2 C 2 O 4 .
[0129] Comparative Example 2
[0130] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the composite lithium supplement material comprises a lithium-rich material, a dispersant and a catalyst, and the dispersant and the catalyst are mixed and coated with the lithium-rich material.
[0131] Comparative Example 3
[0132] This comparative example provides a composite lithium supplement material. The difference between this comparative example and Example 1 is that the composite lithium supplement material comprises a lithium-rich material, a carbon material and a catalyst, and the carbon material and the catalyst are mixed and coated with the lithium-rich material.
[0133] The parameters of the composite lithium supplement materials provided by Examples 1 to 16 and Comparative Examples 1 to 3 are shown in Table 1:
[0134] Table 1 Parameters of composite lithium supplement materials provided in Examples and Comparative Examples
[0135]
[0136]
[0137] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 16 and the composite lithium supplement materials provided in Comparative Examples 1 to 3 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0138] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to form a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0139] Negative electrode: lithium sheet;
[0140] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF was added 6 , forming an electrolyte, LiPF 6 The concentration is 1 mol / L;
[0141] Diaphragm: Polypropylene microporous separator;
[0142] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0143] The electrochemical performance of each lithium-ion battery assembled in the above lithium-ion battery embodiment was tested under the following test conditions:
[0144] The battery was charged at a rate of 0.1C with a cut-off voltage of 4.7V. The battery was charged at a constant voltage with a cut-off voltage of 4.7V. After the charging process was completed, the battery was allowed to stand for 10 minutes and then discharged at a rate of 0.1C with a cut-off voltage of 2.5V. The charging platform was observed during the charging process to obtain the decomposition voltage of the composite lithium supplement material.
[0145] The positive electrode slurry was mixed into a test sample with a solid content of 80%, and then the viscosity was tested using a viscometer. The test results of the lithium battery and the positive electrode slurry are shown in Table 2 below:
[0146] Table 2. Test results of embodiments and comparative examples
[0147]
[0148]
[0149] From the test results of Example 1 and Comparative Examples 1 to Comparative Examples 3 in Table 2, it can be seen that the present invention can reduce the decomposition voltage and overpotential of the lithium-rich material by mixing the catalyst with the lithium-rich material, so that the lithium-rich material can be decomposed to release capacity. At the same time, the present invention retains the dispersant residue on the outer surface of the lithium-rich material, improves the dispersibility of the lithium-rich material and the composite lithium-supplementing material itself, thereby not only reducing the viscosity of the positive electrode slurry, but also facilitating further reducing the decomposition voltage and overpotential, and the carbon material outside the lithium-rich material improves the conductivity of the lithium-rich material, so that the lithium-rich material can fully release capacity.
[0150] From the test results of Example 1 to Example 3 in Table 2, it can be seen that under the same structure, the lithium-rich material, oligomer, carbon material and catalyst have a great influence on the performance of the composite lithium-supplementing material. When the oligomer is less and the carbon material is more, the viscosity of the positive electrode slurry will increase and the dispersibility will deteriorate. However, due to the large amount of carbon material, the conductivity of the composite lithium-supplementing material is better, and the decomposition voltage and overpotential of the lithium-rich material are reduced. When there are more oligomers and less carbon material, the viscosity of the positive electrode slurry will decrease and the dispersibility will improve. However, due to the small amount of carbon material, the conductivity of the composite lithium-supplementing material is poor, and the decomposition voltage and overpotential of the lithium-rich material are increased.
[0151] From the test results of Example 1, Example 4-Example 5 in Table 2, it can be seen that the coating thickness of the oligomer and the carbon material has an impact on the performance of the composite lithium supplement material. When the thickness is too low, the dispersibility of the composite lithium supplement material is poor. When the thickness is increased, the composite lithium supplement material can be better dispersed and the viscosity of the positive electrode slurry can be reduced. However, due to the increase in the mass proportion of non-lithium materials, the capacity of the composite lithium supplement material will be reduced.
[0152] From the test results of Example 1, Example 6-Example 7 in Table 2, it can be seen that the length of the linear oligomer and carbon material has an impact on the performance of the composite lithium supplement material. When the length is too small, the dispersibility of the composite lithium supplement material is poor and the slurry viscosity increases; when the length is too large, the composite lithium supplement material can be better dispersed and the viscosity of the positive electrode slurry is reduced, but the specific surface area of the material becomes smaller, which affects the conductivity of the composite lithium supplement material and leads to a decrease in capacity.
[0153] From the test results of Example 1, Example 8-Example 9 in Table 2, it can be seen that the depth-to-diameter ratio of the pit has an impact on the electrical properties of the composite lithium supplement material. When the depth-to-diameter ratio of the pit is too small, the uniformity of the catalyst distribution in the outer layer and the contact sites will be reduced, resulting in an increase in the overpotential and decomposition voltage of the lithium-rich material; when the depth-to-diameter ratio of the pit is too large, the catalyst is evenly distributed in the outer layer and the contact sites are abundant, resulting in a decrease in the overpotential and decomposition voltage of the lithium-rich material, and an increase in the capacity of the composite lithium supplement material, but it will affect the structural stability of the composite lithium supplement material.
[0154] It can be seen from the test results of Example 1, Example 10-Example 11 in Table 2 that the particle size of the lithium-rich material affects the dispersion performance and electrical properties of the composite lithium-supplementing material. When the particle size of the lithium-rich material is too small, reaching the nanometer level, the dispersion of the lithium-rich material will deteriorate due to the agglomeration of the nanometers. When the particle size of the lithium-rich material is too large, the dispersion is good, but the lithium-rich material particles are large, the conductivity itself will be worse, and it is difficult to decompose, resulting in an increase in the decomposition voltage and overpotential, and a decrease in capacity.
[0155] It can be seen from the test results of Example 1 and Example 12 in Table 2 that when the surface of the lithium-rich material is flat and has no pits, the contact between the lithium-rich material and the catalyst and the dispersant becomes poor, making the decomposition of the lithium-rich material difficult, resulting in increased overpotential and decomposition voltage of the composite lithium-supplementing material and reduced capacity, but having no effect on the dispersibility of the composite lithium-supplementing material.
[0156] It can be seen from the test results of Example 1 and Example 13 in Table 2 that when the composite lithium supplement material does not have a carbon material, the main impact is on the overpotential of the composite lithium supplement material, which will affect the capacity of the composite lithium supplement material, resulting in a decrease in the capacity of the composite lithium supplement material.
[0157] From the test results of Example 1, Example 14 and Comparative Example 1 in Table 2, it can be seen that the catalyst will affect the decomposition effect of the lithium-rich material. When there is no catalyst, the electrical properties of the lithium-rich material are too poor to release the capacity, but it will not affect the dispersion performance of the composite lithium-supplementing material.
[0158] It can be seen from the test results of Example 1, Example 15-Example 16 in Table 2 that the solution provided by the present invention is also applicable to other types of lithium-rich materials and catalysts, and the composite lithium-supplementing materials have lower decomposition voltage and overpotential, and reduced slurry viscosity, indicating that the composite lithium-supplementing material with a unique structure provided by the present invention has greater advantages over the prior art.
[0159] In the description of the embodiments of the present invention, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0160] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A composite lithium supplement material, characterized in that: The invention comprises a lithium-rich material and a dispersant residue, wherein the dispersant residue is combined on the surface of the lithium-rich material, and the dispersant residue comprises an oligomer, and the molecular weight of the oligomer is 500-10000.
2. The composite lithium supplement material according to claim 1, characterized in that: The dispersant residue further includes a carbon material, which is formed by carbonizing the dispersant. The carbon material and the oligomer are mixed and coated on the surface of the lithium-rich material.
3. The composite lithium supplement material according to claim 2, characterized in that: The oligomer and / or the carbon material are in a linear structure, and / or the oligomer and / or the carbon material are interwoven to form a network structure.
4. The composite lithium supplement material according to claim 3, characterized in that: The lithium-rich material is a porous structure with pits on the surface, and the oligomer and / or the carbon material extends into a plurality of the pits to connect the plurality of pits in series; and / or at least one of the pits contains a portion of the oligomer and / or the carbon material, and the oligomer and / or the carbon material are mixed in the pits.
5. The composite lithium supplement material according to claim 4, characterized in that: The ratio of the depth of the pit to the diameter of the pit is (1-10): (99-90); and / or The length of the linear structured oligomer or the carbon material is 50 nm to 1000 nm; and / or The coating thickness of the carbon material and the oligomer is 50nm to 500nm.
6. The composite lithium supplement material according to claim 2, characterized in that: The composite lithium supplementing material further includes a catalyst, which is combined on a surface of at least one of the lithium-rich material, the oligomer, and the carbon material to form a single-atom film.
7. The composite lithium supplement material according to claim 6, characterized in that: The dispersant residue also includes small molecule organic matter and / or inorganic salt; and / or The catalyst comprises a metal element and / or a metal compound; and / or The mass ratio of the lithium-rich material, the oligomer, the carbon material and the catalyst is (70-97): (5-15): (1-10): (1-5).
8. The composite lithium supplement material according to any one of claims 1 to 7, characterized in that: The particle size of the lithium-rich material is 500nm to 20μm; and / or The lithium-rich material has a porous structure, and the porosity of the lithium-rich material is 20% to 80%; and / or The specific surface area of the lithium-rich material is 500 m 2 / g~2000m 2 / g.
9. A method for preparing a composite lithium supplement material, characterized in that: include: mixing a lithium-rich material with a dispersant to obtain a mixture; calcining the mixture so that at least a portion of the dispersant is converted into a dispersant residue to obtain a composite lithium supplement material; Wherein, the dispersant residue includes oligomers, and the molecular weight of the oligomers is 500 to 10,000.
10. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the composite lithium supplement material according to any one of claims 1 to 8, or comprises the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material according to claim 9.